The effectiveness of intraoperative hypothermia at microsurgery of brain aneurysms - Svitlana Dudukina; Mykola Zorin; Sergiy Grygoruk; Illya Plyushchev (Ukrainian Neurosurgical Journal, 2013)
The purpose: to determine effectiveness of prophylactic systemic hypothermia at surgical treatment of patients with brain arterial aneurysms in the early deferred period of subarachnoid hemorrhage.Materials and methods. 105 patients with aneurysmal subarachnoid hemorrhage were examined. Aneurysm clipping was performed in all patients in the period of arterial spasm regression. The patients were divided into two groups: in 51 of them standard anesthetic management was used, in 54 — surgery was performed under systemic hypothermia. The influence of the patient’s body temperature during surgery on it’s outcomes was estimated.Results. Only intraoperative aneurysm rupture (t=0,41, p<0,001) influenced significantly on results of treatment, there was no correlation with the body’s temperature (t=0,06, p=0,656). At normothermia temporary arteries clipping worsened the outcomes (t=0,50, p<0,001), while at hypothermia it practically didn’t effect them (t=0,21, p=0,023). Bradycardia, arrhythmia, hyperglycemia, hypokalemia were considered specific complications of hypothermia.Conclusions. The patient’s body temperature at intraoperative bleeding does not affect the results of treatment; temporary clipping of cerebral arteries is most safe at hypothermia using; hypothermia application is possible at planning of arteries temporary clipping and at high risk of aneurysm re-rupture; the use of hypothermia effects positively the overall results of patients’ treatment in the early delayed period of subarachnoid hemorrhage.